Reinforcement of Energy Knowledge in Higher Education of African Countries - Sánchez, A; Docampo, D; Cancela, A; Maceiras, R; Alfonsín, V (European Journal of Sustainable Development, 2014)
This paper describes the Project HEEMS (Reinforcement of Higher Education as a tool to foster efficient use of energy applied to the poverty reduction within the marine sector through capacity building and regional integration.). This project is part of the cooperation program Edulink II. Edulink is a Higher Education Cooperation Program of European Union with the ACP Countries (African, Caribbean and Pacific). The principal aim of HEEMS is to improve the know how of knwoledge fields related to the efficient use of energy, and take advantage of small scale use of renewable energies as a tool to the development of marine sector. The countries covered by the project are the African Lusophone Countries (excep Angola), that is: Cape Verde, São Tomé and Principe and Mozambique. Actions proposed are related to Energy Access and Efficiency Higher Studies. Due the University of Vigo expertise on earninig technologies, the learning contents will availables at the University of Vigo Digital Online Campus which is a part of the Campus del Mar: Knowledge in Depth (International Campus of Excellence), at undergraduate, graduate and professional training levels in the fields of renewable energies. Furthermore, ACP HEEMS countries will use the University of Vigo Infrastructure (online education platforms, WebTV, videoconference) and all the material generated by professors at the universities linked to Campus del Mar, even clone totally or partially that infrastructure with the assitance os european technicians. The project will contribute to the training (presential or remotel) of the local trainers, thus allowing new in-person and online teaching programs at the same time. This is project oriented to the training of trainers project.